Does Overconfidence Really Confer Adaptive Benefits to Children’s Learning? - Hu, Mengqi; Zhao, Wenbo; Cao, Meiyuan; Shanks, David R.; Hu, Xiao; Luo, Liang; Yang, Chunliang (Psychological Science, 2026)
Does overconfidence really confer adaptive benefits to children’s learning? Through a tripartite investigation involving a preregistered replication (Study 1; N = 30, children aged 6–8 years), computational simulation (Study 2), and an experimental intervention (Study 3; N = 64, children aged 6–8 years), we first replicated previous findings that highly overconfident (HO) children exhibited less negative performance change across a memory task than their low-overconfidence (LO) counterparts. However, this pattern was driven by participant-selection bias and regression-to-the-mean effects rather than by adaptive benefits of childhood overconfidence. When experimentally manipulating children’s overconfidence levels to eliminate these methodological drawbacks, the difference in performance changes between HO and LO children disappeared. These findings challenge an influential hypothesis about the adaptive nature of childhood overconfidence, underscore the risks of median-split designs with difference scores, highlight the necessity of causal experimental approaches in developmental research, and raise concerns about educational practices promoting positive illusions in children.